2011
DOI: 10.1126/scitranslmed.3003174
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Tenofovir and Emtricitabine in Mucosal Tissues: Implications for Prevention of HIV-1 Transmission

Abstract: A mainstay of strategies to prevent HIV-1 transmission is to use antiretroviral therapy (ART) for pre-exposure prophylaxis (PrEP). Critical to the design and interpretation of PrEP prevention trials is the ability to make accurate pharmacological measurements of ART drugs in human genital and colorectal mucosal tissues, the principal route of HIV transmission. Here, we evaluated two drugs that are preferentially used for PrEP: tenofovir (TFV) disoproxil fumarate (TDF) and emtricitabine (FTC). A single oral dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
318
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(352 citation statements)
references
References 21 publications
24
318
5
5
Order By: Relevance
“…However, the peak levels of drugs secreted in vaginal fluids in macaques following oral tablet treatment are 2 to 3 orders of magnitude lower than the concentrations of FTC and TFV observed 24 h after vaginal RDT application reported here, suggesting that the RDT might be a more effective, and potentially safer, delivery method than oral PrEP. Further comparison with studies evaluating systemic and genital mucosal drug levels in women following oral FTC-TDF treatment shows a similar trend (14), with the FTC and TFV concentrations in that study being comparable to those in pigtailed macaques receiving oral tablets, but the drug levels in vaginal tissues and fluids reported in that study were substantially lower than those reported here with the vaginal RDTs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, the peak levels of drugs secreted in vaginal fluids in macaques following oral tablet treatment are 2 to 3 orders of magnitude lower than the concentrations of FTC and TFV observed 24 h after vaginal RDT application reported here, suggesting that the RDT might be a more effective, and potentially safer, delivery method than oral PrEP. Further comparison with studies evaluating systemic and genital mucosal drug levels in women following oral FTC-TDF treatment shows a similar trend (14), with the FTC and TFV concentrations in that study being comparable to those in pigtailed macaques receiving oral tablets, but the drug levels in vaginal tissues and fluids reported in that study were substantially lower than those reported here with the vaginal RDTs.…”
Section: Discussionmentioning
confidence: 53%
“…There are also other concerns about daily or lifelong oral chemoprophylaxis, such as drug toxicity, HIV drug resistance, and cost-effectiveness. Furthermore, the TFV and tenofovir diphosphate (TFV-DP) concentrations in the vaginal compartment following oral dosing have been shown to be significantly lower than what may be needed to confer protection (14), suggesting that higher oral doses may be necessary for women, thus heightening concerns about systemic toxicity. Local application of microbicides therefore has its advantages and may be preferred over oral PrEP.…”
mentioning
confidence: 99%
“…Consistent with this, we also have not shown OAT1 expression in vaginal biopsy specimens. It has been speculated that low-level OAT1 expression in colonic tissue combined with high colorectal luminal drug concentrations contributed to the 100-fold higher TFV levels in colorectal than vaginal tissue after oral dosing (38,39). The notion that OATs mediate TFV uptake comes primarily from in vitro studies using transfected cells or Xenopus oocytes overexpressing the transporters (15,23,29).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the TFV SP-to-BP concentration ratio appears to be variable depending on the time elapsed between drug intake and sampling. Another study has focused on a TFV single-dose administration and has reported an SP-to-BP exposures ratio of 1.0 (16). However, that study included a small number of subjects (n ϭ 8 men) and examined only the final phase of decay of TFV pharmacokinetics (PK) (from 24 h to 14 days).…”
mentioning
confidence: 99%
“…Available data on tenofovir (TFV) SP concentrations are sparse, although this drug is recommended as a preferred choice in first-line regimens for HIV treatment and postexposure prophylaxis and a large body of evidence from trials using TFV-based regimens now supports the concepts of "treatment as prevention" and "preexposure prophylaxis" (11,12). Four studies have suggested an accumulation of TFV in the male genital tract to different extents (13)(14)(15)(16). Mean TFV SP-to-BP concentrations ratios have been estimated at 2.8 (n ϭ 4 men) and 3.3 (n ϭ 15 men) for various sampling times (13,14).…”
mentioning
confidence: 99%